The Effect of Quality of Life on the Psychological Status among Kidney Transplant Recipients and Donors. - Bulut, Aziz; Karabulut, Demet Gozacan; Bulut, Aliye (International Journal of Caring Sciences)
Aim: The aim of the study is to examine the effect of quality of life on the psychological status in kidney transplant recipients and donors. Materials and Methods: The data were obtained by face-to-face interview method from the participants who applied to Gaziantep University Sahinbey Research and Application Hospital Organ Transplant Center (n=649. A questionnaire was used in the study. The questionnaire consists of three parts. The first part is the personal information form, which constitutes the independent variables of the study and includes questions prepared by the researchers in line with the literature and examining some sociodemographic characteristics of the participants. The second part of the questionnaire consists of the SF- 36 Health Survey Questionnaire (SF-36) and the third part consists of the Depression Anxiety Stress-21 Scale (DASS-2). Results: There was no difference (p>0.05) in the subscale scores of the SF-36, the DASS-21 and subscale scores and the age and BMI distributions of the participants whether or not they were kidney transplant recipients or donors (p> 0.05). Conclusion: Healthcare professionals should develop interventions and strategies according to the needs of patients for coping methods against other difficulties, especially psychological difficulties, after patients return home after transplantation; they should recognize the difficulties that patients face and may face, and take interventions to alleviate and prevent them. This approach can provide benefits in providing a high quality health care for transplant recipients and donors in the postoperative out-ofhospital processes, thus improving the quality of life of patients.